The use of dynamic sentinel node biopsy in case of penile cancer. A case report - Kempisty, Jakub; Ornat, Mariusz; Ławiński, Janusz; Makara-Studzińska, Marta; Hys, Michał; Stasieczek, Mateusz; Jabłonowski, Zbigniew (Journal of Education, Health and Sport, 2019)
Penile cancer is a rare disease with prevalence of approximately 1/100000 man in Europe. Well documented risk factors for a penile cancer are HPV Infection, phimosis, and chronic inflammation. Penile cancer is a curable condition when diagnosed and treated promptly. The invasion of lymphatic system is one of the most important matters affecting long term survival. Proper evaluation and treatment of lymph nodes is a main goal when dealing with this condition. In patients with palpable lymph nodes lymphadenectomy is method of choice. When dealing with unpalpable lymph nodes and increased risk of micro-metastatic disease, invasive nodal staging is recommended. For this staging we can choose from Modified inguinal lymphadenectomy and Dynamic Sentinel Node Biopsy In this paper we would like to present a case report of patient with penile cancer, where due to TNM staging, Dynamic Sentinel Node Biopsy was implemented.